Axial compressive stress–strain model for hybrid-reinforced concrete columns with FRP ties. Issue 3 (2nd March 2022) - Tahir, Muhammad; Isleem, Haytham F.; Wang, Zhenyu
Abstract : The use of fibre-reinforced polymers (FRPs) as internal confining reinforcement in combination with longitudinal steel bars in concrete compression members provides significantly improved strength, ductility and durability. To date, only a few experimental studies have been carried out to establish the compressive behaviour of concrete columns longitudinally reinforced with steel bars and confined with FRP ties. This paper provides a confinement model with several expressions for predicting the axial stress–strain response of hybrid-reinforced (i.e. longitudinal steel bars combined with FRP ties) square concrete columns under axial compression loading. The model considers the influences of several test parameters, such as the configuration, size, volumetric ratio, spacing and type of ties (FRP pultruded bar ties and closed-type wound rectangular-section ties). The proposed model predicted well the peak and ultimate strength and strains compared with existing models. The overall accuracy of the model was also assessed against selected test stress–strain responses.